Inclusiveness of Women’s Empowerment in Muslim Societies - Paracha, Kalsoom; Khalid, Aiman (Islamic Studies, 2023)
This article engages contemporary scholarly literature on women’s empowerment in Muslim societies, examining various indicators and challenges to women’s empowerment and analyzing case studies to assess the effectiveness of different strategies and initiatives. Furthermore, the research explores the norms of women’s empowerment from the perspective of Abrahamic religions, arguing that, despite having historically patriarchal norms, these religions actively worked towards promoting gender equality. In Muslim societies, cultural practices and interpretations limited women’s autonomy. Ongoing efforts within Islamic scholarship and activism strive to reconcile these practices with Islamic values and advance gender equality. Despite notable progress in recent times, the findings highlight cultural, legal, and institutional barriers that hinder women from realizing their full potential. To overcome these obstacles, this article suggests operating within existing cultural and religious frameworks to challenge gender stereotypes and encourage fair gender relations. Ultimately, the article emphasizes the importance of increased collaboration and knowledge-sharing to prioritize women’s empowerment as a fundamental development goal. By creating an environment that fosters the full participation and inclusion of women in all aspects, Muslim societies can unlock the immense potential of their female population, leading to sustainable development and social progress for all.